60 Rooms with a View. (Amsterdam : Art Hotel Foundation, 1994)
Schnider, Albrecht ; Bleek, Cornelia Schmidt ; Graumann, Hervé ; de Steeg, Niek Van ; Klamer, Stan ; Lamers, Kiki ; Schmacke, Claudia ; Abramovic, Marina ; Hill, Christine ; Peeters, Stijn ; Moylan, Donna ; Kruk, Mariusz ; Mangos, Simone ; Kloosterboer, Klaas ; Hyde, James ; Hepworth, Stephen ; Bourgeau, Jef ; Images, Philippe Mairesse / Grore ; Chiezo, Taro ; Bustamente, Jean-Marc ; Schulze, Gundula ; Bijtebier, Jean-Marie ; Quinn, Marc ; Faucheur, Jean ; Nanney, Chuck ; Gallace, Maureen ; Donegan, Cheryl ; Birza, Rob ; Munoz, Oscar ; Mendieta, Ana ; François, Michel ; Gjerdevik, Nils Erik ; Everaert, Patrick ; McGovern, Tom ; Medina, Lazaro Garcia ; Droese, Felix ; Wörsel, Troels ; Fortuyn/O'Brien ; Newman, Chris ; Collective, Unknown ; Scarpa, Michel ; Woodruff, Thomas ; Valldosera, Eulàlia ; Geismar, Jarg ; Doberauer, Anke ; Sinha, Sanjeev ; Vigouroux, Christophe ; Dormitzer, Spencer ; Milloff, Mark ; Creten, Johan ; Jonas, Joan ; Blazy, Michel ; Bublex, Alain ; Dreher, Ruprecht ; Claassen, Tom ; Semah, Joseph ; Knöfel, York der ; Sajet, Philip
biografie
60 Rooms with a View, Art Hotel - The Amsterdam Hilton Hotel, February 9-13, 1994
kunstcatalogus